2015
DOI: 10.1249/jsr.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Jet Lag Modification

Abstract: Athletes often are required to travel for sports participation, both for practice and competition. A number of those crossing multiple time zones will develop jet lag disorder with possible negative consequences on their performance. This review will discuss the etiology of jet lag disorder and the techniques that are available to shorten or minimize its effects. This includes both pharmacological and nonpharmacological approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 7 publications
0
24
0
1
Order By: Relevance
“…Multiple variables can influence recovery, such as nutrition [13], sleep [47], and travel [4, 8]. In many team sports, there is limited opportunity to recover owing to high training/competition loads [9] and vigorous travel schedules (e.g., baseball, basketball, ice hockey, and soccer), which can involve inconsistent sleep schedules, time zone changes [8], and changes in altitude [10]. In addition to these issues, team sport training/competition presents significant mechanical loads (particularly contact sports, e.g., American football, rugby, and ice hockey) and metabolic demands that cause fatigue and pose challenges to the recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple variables can influence recovery, such as nutrition [13], sleep [47], and travel [4, 8]. In many team sports, there is limited opportunity to recover owing to high training/competition loads [9] and vigorous travel schedules (e.g., baseball, basketball, ice hockey, and soccer), which can involve inconsistent sleep schedules, time zone changes [8], and changes in altitude [10]. In addition to these issues, team sport training/competition presents significant mechanical loads (particularly contact sports, e.g., American football, rugby, and ice hockey) and metabolic demands that cause fatigue and pose challenges to the recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…'Travel fatigue' is a condition frequently experienced by travelers on any long-distance journey and is not associated specifically with air travel across time zones (Simmons, McGrane, & Wedmore, 2015). 'Travel fatigue' has been extensively studied in sports medicine, and defined as a more complex summation of physiological, psychological, and environmental factors that accrue during an individual trip (Samuels, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the negative effects on perception could be due to sleep deprivation and other sleep disturbances induced during the experiments, such as the social jet lag that occurred due to the change in the sleep and wake times. Social jet lag refers to a change in sleeping hours, for example, from workdays to non-working days (Wittmann et al, 2006;Simmons et al, 2015;Malhotra, 2017), and has been reported to affect postural control . Also, jet lag is the term applied to a group of symptoms that exist transiently after undergoing a rapid time-zone transition, and it has been reported that this situation negatively affects physical and cognitive performance (Davenne, 2009;Edwards and Waterhouse, 2009).…”
Section: Before Exercise After Exercisementioning
confidence: 99%
“…"social jet lag") refers to a change in sleeping hours (e.g. it is very common to change sleeping hours from workdays to non-working days) (Wittmann et al, 2006;Simmons et al, 2015;Malhotra, 2017). For example, it has been reported that social jet lag affects postural control by a negative effect on brain areas (e.g.…”
Section: Introductionmentioning
confidence: 99%